Quantifying national biomechanics day's impact on student perceptions toward biomechanics: A multisite pilot study. (January 2022) - Monfort, Scott M.; Bigelow, Kimberly E.; Vallabhajosula, Srikant; Evertz, Loribeth Q.; Becker, James N.; Wittstein, Matthew W.; Gannon, Paul; DeVita, Paul
Abstract: National Biomechanics Day (NBD) is an international celebration of biomechanics that seeks to increase the awareness and appreciation of biomechanics among the high school community. Initial research supports the positive effects of NBD on students' attitudes toward the field of biomechanics; however, quantitative evidence remains scarce. The purpose of this study was to quantify changes in high school students' perceptions toward biomechanics after participating in NBD events to better understand the impact of NBD. Data were collected at two locations during the 2019 NBD season. Surveys were collected before and after NBD events for 112 high school students from Montana and North Carolina. Paired pre- versus post-NBD surveys for the aggregate sample population suggest that students perceived biomechanics as more appealing ( p  = 0.050), exciting ( p  = 0.007), and important ( p  = 0.018) following the NBD events. Students did not report a change in whether they could see themselves in a biomechanics-related career ( p  = 0.49). These findings further support the ability for NBD events to positively impact students' perceptions toward biomechanics, although opportunities persist to increase student career interest in biomechanics. This paper presents and discusses the study's results, interpretations, limitations, and implications for future research on biomechanics outreach activities.